The characteristics and controlling factors of glutenite reservoirs in the Permian Upper Urho Formation, southern Zhongguai Rise, Junggar Basin, NW China. Issue 1 (19th October 2021) - Chen, Hongfei; Lv, Qijun; Gao, Jun; Yu, Jingfeng; Pang, Yanqing; Li, Bin; Zheng, Aiping; Ju, Shichang; He, Naixiang; Luo, Shuai; Wang, Xiaoqiang
Abstract : The southern Zhongguai Rise, the petroliferous zones in northwestern Junggar Basin, is among the most significant sedimentary basins in China because of its abundant petroleum reserves. The reservoir characteristics and their responses to controlling factors have been complex in the Permian Upper Urho Formation. A systematic investigation has been conducted based on integrated analysis of seismic volumes, wireline logs, mud logs, cores, thin sections, SEM, grain size data, porosity‐permeability data, and mercury injection test results. The results indicate that the Upper Urho Formation consists of five types of lithology (glutenite, coarse‐grained sandstone, medium‐grained sandstone, fine‐grained sandstone, and siltstone). Furthermore, the detrital composition in Upper Urho Formation is predominantly composed of debris (mainly volcanic rocks), with relatively less contents of quartz and feldspar. The cement is dominated by calcite, laumontite, and siliceous. In addition, the reservoir space in Upper Urho Formation includes intergranular pore, intragranular pore, dissolution pore, and microfracture. The intergranular pore and dissolution pore comprise the main reservoirs. The reservoirs in Upper Urho Formation are characterized by micro‐fine pore‐throat and low‐porosity permeability. Diagenesis along with sedimentary facies exerts the controls on the reservoir heterogeneity and physical properties. Abstract : The thin sections (including casting thin section and fluorescence thin sections) and SEM showing the characteristics of reservoir spaces (residual intergranular pore, intragranular pore, dissolution pore, and microfracture).